A modular platform based on electrospun carbon nanofibers and poly(N‐isopropylacrylamide) hydrogel for sensor applications. (17th August 2021) - Bongiovanni Abel, Silvestre; Martinez, María V.; Bruno, Mariano M.; Barbero, Cesar A.; Abraham, Gustavo A.; Acevedo, Diego F.
Abstract : Modular sensor platforms are a fashion approach that allows the use of advanced materials to promote the evolution of portable electrochemical sensors. A modular platform building by the combination of carbonized poly(acrylonitrile) electrospun mat (C‐PAN; fiber diameter ca. 300 nm) and a poly( N ‐isopropylacrylamide; PNIPAm) hydrogel was assayed. The individual components of the platform were physicochemically characterized before assembling. The swelling behavior and the capacity of sorption of a redox complex tris(1, 10‐phenanthroline)iron(II) of the polymeric hydrogel were evaluated. Moreover, the morphological aspects of the electrospun fibers before and after carbonization were analyzed. Finally, cyclic voltammetry and chronocoulometry experiments were performed to analyze the electrochemical performance of the modular platform. In this work, we demonstrated that the platform takes advantage of the3D structure of the electrospun mat and the selective sorption of the hydrogel for the electrochemical sensing target analyte. The iron sensing using its complexation into the tris(1, 10‐phenanthroline)iron(II) redox complex was assessed by differential pulse voltammetry (DPV). The anodic peak current showed a linear relation versus iron complex concentration in the range of 10–80 μmol L −1 with a detection limit of 0.103 μmol L −1 . All the results herein presented suggest that a synergistic combination of large surface area carbon fiber electrodes and ion retaining hydrogel has been achieved.